2D/3D local strain analysis of layered metal composites with a strength-ductility synergy. (August 2019) - Li, D Y; Huang, M; Xia, Y P; Xu, C; Gan, W M; Geng, L; Fan, G H
Abstract: A long-standing question is why layered structures can overcome the strength-ductility trade-off and achieve synergy in this relationship. In this paper, layered Ti/Al, Ti/Ti metal materials are taken as examples to investigate the influence of a heterogeneous layered structure on their deformation behavior from a viewpoint of the local strain. In-situ neutron diffraction, DIC and synchrotron radiation tomography were performed to obtain lattice strain evolution (elastic stage), local strain evolution (plastic stage), and crack initiation and propagation (fracture stage), respectively. It is found that strain delocalization is the key to achieving a strength-ductility synergy in layered materials, and that layered structures can influence the local strains from start to failure, which improves strain compatibility between the component layers. In-situ tracking of local strains based on 2D/3D characterization methods during entire deformation process deepens our understanding of the deformation behavior of layered materials.